Emitter ballasting resistor design of InGaP/GaAs power HBT for high linearity based on Volterra Series distortion analysis. (June 2018) - Zhang, Xiaodong; Sun, Xiaohong; Wang, Feng; Tian, Ting; Gao, Huai
Abstract: A distortion analysis of InGaP/GaAs HBT is presented based on Volterra Series. The interdependence between emitter ballasting resistor and linearity has been quantitatively analyzed. An optimized emitter ballasted power amplifier (PA) is designed and fabricated. Third-order intermodulation (IM3) of the PA is suppressed by 3–8 dB without sacriﬁcing power gain and PAE. The theoretical calculation and measurement results show the optimization of emitter ballasting resistor is an alternative technique to improve PAs' linearity.